1991
DOI: 10.1067/mva.1991.26137
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preservation or perfusion of intraoperatively identified spinal cord blood supply on spinal motor evoked potentials and paraplegia after aortic surgery

Abstract: Permanent ligation of arteries supplying blood to the spinal cord in operations for aortic aneurysm can lead to spinal cord ischemia, which can result in either paraparesis or paraplegia. This report describes a rapid method of intraoperative identification of those arteries that supply the spinal cord by use of an intrathecal platinum electrode to detect hydrogen in solution that has been injected into the aortic ostia. Preservation or perfusion of those identified arteries supplying the spinal cord may decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
1
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(69 citation statements)
references
References 13 publications
0
66
1
2
Order By: Relevance
“…169 , em estudo não controlado, tenham sugerido que a naloxona associada à drenagem de LCR possa até mesmo dispensar o reimplante de artérias intercostais, nenhum benefício desta técnica foi evidenciado em ensaio randomizado subseqüente 171 , o que torna seu uso empírico.…”
Section: Aorta Descendente -Toraco-abdominalunclassified
“…169 , em estudo não controlado, tenham sugerido que a naloxona associada à drenagem de LCR possa até mesmo dispensar o reimplante de artérias intercostais, nenhum benefício desta técnica foi evidenciado em ensaio randomizado subseqüente 171 , o que torna seu uso empírico.…”
Section: Aorta Descendente -Toraco-abdominalunclassified
“…Although Acher et al [143] in a non-controlled study suggested that naloxone associated with CRL drainage can even dispense with the re-implantation of intercostal arteries; no benefits of this technique were evidenced in subsequent randomized trials [166] making its use empirical.…”
Section: Descending Aorta -Thoracic-abdominalmentioning
confidence: 99%
“…3,16,17 Kouchoukos 18 reported a correlation to exist between paraplegia and the time of clamping and the length of harvested aorta. However, the reimplantation of the intercostals to the graft as far as possible is one of the best methods of protection, and especially all possible intercostals and lumber arteries between T6 and L1 should be reimplanted to the graft as far as possible.…”
Section: Discussionmentioning
confidence: 97%
“…3 Different studies have been carried out about to identify the ASA and ARM and placement of clamps under these arteries. 16 Svensson et al 16 identifi ed these arteries by a special method perioperatively by which the incidence of paraplegia after their operations decreased. Yamada et al 19 preoperatively revealed the ASA, ARM, and critical intercostal arteries by magnetic resonance angiography.…”
Section: Discussionmentioning
confidence: 99%